SYNTACTICALLY BOUND CONSTRUCTION «GO + AND + V» IN THE MODERN ENGLISH LANGUAGE (Proceedings of Southern Federal University. Philology, 2013)
Gurikova Yu. S.Keywords: syntactic phraseology, syntactic phraseological units, loss of actuality, desemantization, phraseological meaning.The article is devoted to the analysis of the syntactically bound construction of the English language which functions as the predicate of the sentence. This construction is one of the variations of syntactic phraseological units. Like all the syntactic phraseological units, this construction is simultaneously connected with the syntactic and phraseological levels of the language. The peculiarity of this construction is a full loss of grammatical and semantic actuality of one of the components. The article examines the main features of the construction, its syntactic phraseological meaning, anomalies, confirmation the phraseological character of the unit.